Influence of pine sawdust on SO2 retention by CaO in coal slime briquette. Issue 16 (18th August 2017) - Lu, Guangjun; Zhang, Kai; Cheng, Fangqin
ABSTRACT: Coal slime, coal slime/CaO, and coal slime/CaO/pine sawdust were formed to make briquettes respectively. The effects of pine sawdust on the SO2 retention by CaO during coal slime briquette combustion were studied using a tube furnace. The obtained results demonstrated that porous structures were created in the briquette residue in the case of pine sawdust addition, and more sulfur retention product, CaSO4, was obtained in both outer and inner briquette residue. In addition, increasing combustion temperatures had a negative impact on SO2 reduction. In the experiments, SO2 retention efficiency achieved 48.3% when biomass and CaO were added to coal slime briquette at 850°C. It indicated that pine sawdust improved the reaction efficiency of CaO capturing SO2 in the coal slime briquette. The addition of CaO with pine sawdust is a dependable way for reliable reduction of SO2 .